Serological Evidence of Hepatitis E Virus (HEV) Infection Among Ruminant Farmworkers: A Retrospective Study from Malaysia - Wong LP; Tay ST; Chua KH; Goh XT; Alias H; Zheng Z; Zhao Q; Wu T; Xia N; Hu Z; Lin Y (Infection and Drug Resistance, 2022)
Li Ping Wong,1,2 Sun Tee Tay,3 Kek Heng Chua,4 Xiang Ting Goh,4 Haridah Alias,1 Zizheng Zheng,5 Qinjian Zhao,6 Ting Wu,5 Ningshao Xia,5,7 Zhijian Hu,2 Yulan Lin2 1Centre for Epidemiology and Evidence-Based Practice, Department of Social and Preventive Medicine, Faculty of Medicine, Universiti Malaya, Kuala Lumpur, 50603, Malaysia; 2Department of Epidemiology and Health Statistics, School of Public Health, Fujian Medical University, Fuzhou, Fujian, 350122, People’s Republic of China; 3Department of Medical Microbiology, Faculty of Medicine, Universiti Malaya, Kuala Lumpur, 50603, Malaysia; 4Department of Biomedical Science, Faculty of Medicine, Universiti Malaya, Kuala Lumpur, 50603, Malaysia; 5State Key Laboratory of Molecular Vaccinology and Molecular Diagnostics, National Institute of Diagnostics and Vaccine Development in Infectious Diseases, School of Public Health, Xiamen University, Xiamen, 361102, People’s Republic of China; 6College of Pharmacy, Chongqing Medical University, Chongqing, People’s Republic of China; 7The Research Unit of Frontier Technology of Structural Vaccinology of Chinese Academy of Medical Sciences, Xiamen University, Xiamen, 361102, People’s Republic of ChinaCorrespondence: Yulan Lin, School of Public Health, Fujian Medical University, Fuzhou, Fujian, 350122, People’s Republic of China, Email yulanlin@fjmu.edu.cn Li Ping Wong, Faculty of Medicine, Universiti Malaya, Kuala Lumpur, Malaysia, Email wonglp@ummc.edu.myBackground: As scant data are available about Hepatitis E virus (HEV) infection in Malaysia, this study aimed to determine the seroprevalence of HEV amongst ruminant farmworkers in Malaysia.Methods: A total of 87 farmworkers provided serum samples, which were collected from eight farms. All serum samples were tested for anti-HEV IgG and anti-HEV IgM by an enzyme-linked immunosorbent assay (ELISA) using the Wantai HEV-IgG and HEV-IgM ELISA kits from Beijing Wantai Biological Pharmacy Enterprise Co., Ltd, Beijing, China.Results: Farmworkers from six cattle farms, one sheep farm and one goat farm were investigated in this study. Only one farm practices zero-grazing, with the rest using rotational grazing. Of the 87 farmworkers, males comprised 83.9%, and almost half (47.1%) were aged 20– 35 years old. By ethnic group, the vast majority were Malay. Most of the farmworkers have good hygiene practices; washing or changing their clothes and showering after dealing with farm animals were common. None of the farmworker serum samples had anti-HEV IgM and IgG detected (95% confidence interval (CI): 0, 0.0415).Conclusion: The finding suggests that the farmworkers had no previous exposure to Hepatitis E, and were not at risk of occupational exposure to HEV infection. Our findings suggest that a zero seroprevalence of HEV infection among ruminant farmworkers in the Muslim majority country. Good farm management, hygiene practices and the absence of contact with swine-related contamination might have contributed to the no or minimal zoonotic risks of HEV amongst farmworkers surveyed in this study.Keywords: HEV, farmworkers, seroprevalence, antibody